A bioanalytical method for quantification of telmisartan in rat plasma; development, validation and application to pharmacokinetic study - AL-japairai, Khater Ahmed Saeed; Chatterjee, Bappaditya; Mahmood, Syed; Almurisi, Samah Hamed (A and V publication, 2021)
The telmisartan was determined in a rat plasma using developed and validated a reversed-phase high performance liquid chromatographic (HPLC). The pre-treatment of the plasma sample involving liquid-liquid extraction using ethanol as the extracting solvent. The HPLC method validation has been shown a linear calibration curve over a plasma concentrations range of 0.7 to 10µg/mL with a correlation coefficient of 0.9979, the limit of detection and the limit of quantification were determined to be 0.025µg/ml and 0.07µg/ml, respectively. The precision and accuracy were in an acceptable limit. The pharmacokinetic parameters of telmisartan were adequately evaluated following a single oral dose (4mg/kg) in Sprague-Dawley rats. The results observed conclude that the developed bioanalytical HPLC method is appropriate and applicable as an analytical tool in the pharmacokinetic study of telmisartan.